Epidemiology of shoulder and elbow pain in youth baseball players? - Matsuura, T.; Suzue, N.; Iwame, T.; Arisawa, K.; Fukuta, S.; Sairyo,K. (The Physician and Sportsmedicine, 2016)
Objectives: There are relatively few published epidemiological studies examining the differences in the risk of shoulder and elbow pain in young baseball players. The purpose of this study was to investigate risk factors for shoulder and elbow pain in child and adolescent baseball players.